IMPLEMENTASI ADMINISTRASI DAN PEMBUKUAN PEMBIAYAAN DI KOPERASI SYARIAH - Siti Nurul Amaliyah; Ifatur Rohmah; Moch. Fahmi Rizki; Sri Mulyani; Avita Badiatus (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
The purpose of this study was to determine the implementation of administration and financial bookkeeping in Koperasi Murni Amanah Sejahtera Malang City. This research is a qualitative research with a descriptive approach. Data collection techniques in this study using observation, interviews and documentation. The result of this research is that in the implementation of administrative financing and bookkeeping financing in Koperasi Murni Amanah Sejahtera Malang City prioritizes the principle of prudence because in this case the administration of financing is an inseparable part of the financing activity itself. Implementation of financing administration and bookkeeping carried out at Koperasi Murni Amanah Sejahtera Malang City include the making of a Financing Approval Confirmation Letter (SP3), administration and bookkeeping of financing contracts, administration and bookkeeping of collateral binding, administration and bookkeeping of collateral insurance cover closure, administration and bookkeeping disbursement (Disbursement of Financing).